The impact of Split Share Structure Reform on Earning Management and Audit Quality: Evidence from China - Satybaldina, Ayauly (2017)
This paper aims to investigate the earning management activities in Chinese listed firms where capital market, ownership structure and motivations to manipulate profits that are different from other countries. Specifically, it will attempt to examine the impact of the Split Share Structure reform on earning management and audit quality in China, where, the research investigating the effect of split share structure reform on audit quality is limited. The main difference that distinguished the Chinese market from other stock markets was the establishment of twotier share structure divided into tradable and non-tradable shares. However, the dominance of non-tradable shares led to ineffective functioning of Chinese stock market, which accelerated incentives to earning management. After the split share reform, it is said corporate structure and earning quality of firms’ has improved. However, other authors have the opposite opinion. This study examines 1) the effect of split share reform on accruals from share nature (tradable and nontradable) perspective across three time periods; 2) and monitors the impact split share reform on audit quality.